Halitosis and the Tonsils: A Review of Management. (October 2014) - Ferguson, Matthew; Aydin, Murat; Mickel, Joseph
Objective: Halitosis secondary to pathology of the palatine tonsils is considered airway (type 2) halitosis in the etiologic classification. Reports differ as to the proportion of objective halitosis complaints that have tonsillar etiology, with some giving this figure as 3%. Due to their immunologic role, even healthy tonsils usually possess some subclinical inflammation. The tonsil crypt system is also the most ideal environment for anaerobic bacterial activity in the upper respiratory tract. Tonsillar halitosis is thought to occur mainly because of chronic caseous tonsillitis and tonsillolithiasis (tonsil stones). Tonsillectomy and various cryptolysis techniques are reported to improve halitosis in such cases. In this article, diagnostic methods and evidence for interventions are reviewed. Data Source: Medline search. Review Methods: Studies reporting the efficacy of any intervention (medical or surgical) on tonsillar halitosis were included, whether halitosis was the focus or one of several measures. Conclusions: There are insufficient high-quality studies on this topic. Improved methodology, for example, use of control groups and utilization of more accurate halitosis detection/quantification techniques, are required. Implications for Practice: Lack of evidence currently prevents firm conclusions, but the following is recommended: (1) Use reliable methods for halitosis diagnosis and confirmation of tonsillar etiology. Initial treatment such as tongue scraping is useful to rule out oral halitosis. (2) Tonsillar procedures are contraindicated in: subjective halitosis, non-tonsillar etiology, or if medical management resolves halitosis. (3) Where indicated and where facilities permit, less invasive techniques such as laser cryptolysis may be preferable to tonsillectomy in adults, potentially avoiding general anesthetic and the higher risk associated with tonsillectomy in this group.